Vegetable oils as sustainable inks for additive manufacturing: a comparative study - Vázquez-Martel, Clara; Becker, Lukas; Liebig, Wilfried V.; Elsner, Peter; Blasco, Eva (ACS sustainable chemistry & engineering, 2021)
The use of biobased materials in additive manufacturing is arising as a promising approach to modernize the polymer industry reducing its environmental impact. Herein, novel sustainable formulations are developed for digital light processing (DLP) using five vegetable oils─sunflower, canola, soybean, olive, and sesame oil─as feedstock. These vegetable oils are successfully modified incorporating photopolymerizable groups, i.e., acrylates, enabling printability. The oil-based formulations consisting of a functionalized oil and a photoinitiator are employed as inks for DLP without the need for further additives. The rheology and curing behavior of all the inks and printed materials are carefully investigated. The values obtained for their critical curing energy (Ec) range from 14.52 to 18.49 mJ cm-2, allowing for fast printing. Interestingly, it is found that Ec not only correlates with the average number of acrylate groups per molecule but also the viscosity plays a key role. Additionally, the thermal and mechanical properties are studied and compared. In summary, sunflower and canola oil derivatives offer a better cost-performance ratio than the state-of-the-art soybean oil inks and can be employed for 3D printing of complex geometries with high speed and resolution. This work demonstrates the potential of using biobased and inexpensive materials as high performance inks for DLP 3D printing and opens new possibilities for the next generation of sustainable 3D printing.